1992
DOI: 10.1210/en.131.2.669
|View full text |Cite
|
Sign up to set email alerts
|

Insulin regulation of messenger ribonucleic acid for the surfactant- associated proteins in human fetal lung in vitro

Abstract: Respiratory distress syndrome (RDS) is primarily caused by an immaturity in the synthesis and secretion of surfactant by the fetal lung type II cell. Fetal hyperinsulinemia associated with maternal diabetes places the newborn at an increased risk of developing RDS, and therefore, it has been hypothesized that insulin inhibits type II cell differentiation. We have previously shown that insulin inhibits the accumulation of surfactant-associated protein A (SP-A), the major surfactant-associated protein, in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 0 publications
0
30
1
Order By: Relevance
“…In fetal rat lung explants, no consistent alteration in SP-A mRNA content was observed at different glucose concentrations (24). Insulin at pharmacological doses inhibited surfactant protein A gene expression in vitro (25,26).…”
Section: Ferná Ndez-real and Associatesmentioning
confidence: 93%
“…In fetal rat lung explants, no consistent alteration in SP-A mRNA content was observed at different glucose concentrations (24). Insulin at pharmacological doses inhibited surfactant protein A gene expression in vitro (25,26).…”
Section: Ferná Ndez-real and Associatesmentioning
confidence: 93%
“…Total RNA was isolated from whole lung tissue obtained at 0, 6, 10, 12, and 16 d postnatal age using RNAzol as described previously (18). Ribonuclease protection analysis was used to quantify the steady-state levels of the platelet-derived growth factor receptor ␣ (PDGF-R␣) mRNA in lung tissue from wild-type and RAR␤ null mice at various postnatal ages.…”
Section: Alveolarization In Rar␤ Null Micementioning
confidence: 99%
“…The human fetal lung explant system has been used to study type II alveolar cell differentiation (16), the hormonal regulation of gene expression (17,23), the effects of GC on lung structure (17), as well as the metabolism of GC (24). We observed that HSD2 is expressed at discrete sites in the undifferentiated human fetal lung tissue.…”
Section: Discussionmentioning
confidence: 94%